Sobre a presença de Conus pulcher (Lightfoot), 1756 na gruta das Fontainhas (Cadaval) ou a ocorrência de objectos exóticos africanos em Portugal no decurso do século XVI - Cardoso, João Luís (2020)
We present the study of two specimens of Conus pulcher (Lightfoot), 1786, whose geographical distribution extends from the coast of Mauritania to the Gulf of Guinea, collected in the archaeological excavations carried out in 1879/1880 in the cave of Fontainhas ( Lisbon District, Cadaval municipality). The dating obtained by radiocarbon preferably places the age of the specimens between the last quarter of the 15th century and the mid‑17th century. Thus, both the chronology and the geographic distribution of these specimens are compatible with the production, both in the Sierra Leone region and in Benin, of ivory pieces that supplied the Kingdom and the courts of Europe as sumptuous and exotic products. The presence in Portugal of this two shells can thus be explained by being exotic pieces that aroused interest, even by their beauty. However, the reason for their intentional deposition in a cave set up in a deserted place, such as the culminating platform of the Montejunto mountain remains unknown.